Peningkatan Produksi Bawang Merah (Allium Ascalonicum L.) Dengan Pemberian Pupuk KCL dan MuLsa - Gunawan Tabrani; Rlwanl Arisantl; Gusmawartati ' (Jurnal Sagu, 2005)
Onion productivity in Riau was reached 6.1 ton/ha, whereas Indonesian onion productivity has reached 12.3ton/ha, and potential productivity of onions is 14.4 ton/ha. This less onions productivity in Riau is mainlycaused by environmental factors such as climate, the lack of mulch or fertilized calcium. Therefore, toincrease onion productivity in Riau we can use some types of mulch and calcium applying together. A goal ofthis experiment is to increase Riau onion productivity. This experiment had done in the farm of the.AgriculmreFaculty, Riau University in October to December 2003. The experiment was designed with CompletelyRandomized Design in factorial, and the treatment combinations were replicated three times. These factorswere types of mulch in the levels: Without mulch (m,), Grass mulch (nij), Transparence Plastic Mulch (ra,),Black and Silver Plastic Mulch (m^), and doses of Calcium fertilizer in the levels: Without Calcium (K„) and234 lig KCl/ha (K,). The response variables were: sum of slices in each plant, manure weight of the plant perplot (g), dry weight of the plant per plot (g), diameter of hiber (mm), and consumer product per plot (g).Resultsof the experiment showed that there is no interaction between the types of mulch and doses of Catciiun C 'U/hiU-fertilizer in the response variables. The effect of tlic treahncnt combinations could be observed by the types ofmulch only. Black and Silver Plastic Mulch increased the productivity to 9.S ton/ha. This treatment couldincrease manure weight of the plant per plot about llM.6%,dry weight of plan per plot 117.4%, diameter oftuber 27.8%, and consumer product per plot T20,l % when compared to onion without mulch.